Curcumin, an active component of turmeric (Curcuma longa), and its effects on health. Issue 13 (2nd September 2017) - Kocaadam, Betül; Şanlier, Nevin
ABSTRACT: Turmeric ( Curcuma longa ) is a type of herb belonging to ginger family, which is widely grown in southern and south western tropical Asia region. Turmeric, which has an importance place in the cuisines of Iran, Malesia, India, China, Polynesia, and Thailand, is often used as spice and has an effect on the nature, color, and taste of foods. Turmeric is also known to have been used for centuries in India and China for the medical treatments of illnesses such as dermatologic diseases, infection, stress, and depression. Turmeric's effects on health are generally centered upon an orange-yellow colored, lipophilic polyphenol substance called "curcumin, " which is acquired from the rhizomes of the herb. Curcumin is known recently to have antioxidant, anti-inflammatory, anticancer effects and, thanks to these effects, to have an important role in prevention and treatment of various illnesses ranging notably from cancer to autoimmune, neurological, cardiovascular diseases, and diabetic. Furthermore, it is aimed to increase the biological activity and physiological effects of the curcumin on the body by synthesizing curcumin analogues. This article reviews the history, chemical and physical features, analogues, metabolites, mechanisms of its physiological activities, and effects on health of curcumin.